2005
DOI: 10.1002/jcp.20460
|View full text |Cite
|
Sign up to set email alerts
|

3,5,3′‐triiodothyronine (T3) is a survival factor for pancreatic β‐cells undergoing apoptosis

Abstract: 3,5,3'-triiodothyronine (T3) is essential for the growth and the regulation of metabolic functions, moreover, the growth-stimulatory effect of T3 has largely been demonstrated and the pathways via which T3 promotes cell growth have been recently investigated. Type 1 diabetes (T1D) is due to the destruction of beta-cells, which occurs even through apoptosis. Aim of our study was to analyze whether T3 could have an antiapoptotic effect on cultured beta-cells undergoing apoptosis. We have demonstrated that T3 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 51 publications
11
73
0
Order By: Relevance
“…Our evidence suggested the involvement of the PI3K pathway in mediating this novel survival action of T 3 ; in particular, we have shown that T 3 is able to induce the phosphorylation of Akt in the islet cells hCM and rRINm5F (Verga Falzacappa et al 2006). Additionally, Cao et al (2005) have demonstrated that T 3 is specifically able to activate Akt in a non-genomic manner.…”
Section: Introductionsupporting
confidence: 51%
“…Our evidence suggested the involvement of the PI3K pathway in mediating this novel survival action of T 3 ; in particular, we have shown that T 3 is able to induce the phosphorylation of Akt in the islet cells hCM and rRINm5F (Verga Falzacappa et al 2006). Additionally, Cao et al (2005) have demonstrated that T 3 is specifically able to activate Akt in a non-genomic manner.…”
Section: Introductionsupporting
confidence: 51%
“…Thyroid hormone replacement is associated with a decrease in HbA1c level, which is influenced by increased erythropoiesis rather than by changes in glucose level. The observation of negative correlation between T3 and HbA1c is supported by the views of various authors [17,20,21] who state a derangement of glycemic control in type 2 diabetes which influences the thyroid hormone levels. Furthermore, significant negative correlations were noted between parameters of glycemic control and serum T3 levels respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the study demonstrated that serum T3 may be a reliable index of glycemic control in diabetes mellitus. It has recently been reported that T3 has an anti-apoptotic and protective effect on the pancreatic beta cells [20,21]. T3 activates the PI-3 kinase pathway via thyroid hormone receptor on the beta cell, and stimulates insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thyroid hormones are crucial for myocardial development and they may promote myocardial cell survival. Lack of thyroid hormones in the embryonic stage may induce myocardial cell apoptosis and downregulate the mRNA expressions of functional thyroid hormones receptors (Alisi et al 2005, Verga et al 2006.…”
Section: Discussionmentioning
confidence: 99%